2013
DOI: 10.1155/2013/981638
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in the Endothelial Function and Haemostatic and Inflammatory Parameters in Subclinical and Overt Hyperthyroidism

Abstract: Introduction. The aim of the present study was to compare the levels of circulating markers of endothelial function and low-grade inflammation in patients with subclinical and overt hyperthyroidism (OH) due to Graves disease (GD) and toxic nodular goiter (TNG). Material and Methods. The group studied consisted of 42 patients with GD, 75 patients with TNG, and 39 healthy controls. Results. Circulating markers of endothelial dysfunction were elevated in the patients with both SH and OH, but the concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…However, Itterman et al suggested that the effect of variation in THs levels on BP is only a direct, short‐term effect, since only associations with current and not incident hypertension were found in their study . Thirdly, Poplawska‐Kita A et al suggested that both subclinical and overt hyperthyroidism are related to endothelial dysfunction, which plays an important role in pathogenesis of high BP . Furthermore, a previous study also showed that thyroid function was intrinsically linked to variables of endothelial function in healthy euthyroid subjects .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, Itterman et al suggested that the effect of variation in THs levels on BP is only a direct, short‐term effect, since only associations with current and not incident hypertension were found in their study . Thirdly, Poplawska‐Kita A et al suggested that both subclinical and overt hyperthyroidism are related to endothelial dysfunction, which plays an important role in pathogenesis of high BP . Furthermore, a previous study also showed that thyroid function was intrinsically linked to variables of endothelial function in healthy euthyroid subjects .…”
Section: Discussionmentioning
confidence: 87%
“…Secondly, in endothelial cells, THs can activate endothelial NO synthase through the PI3K/Akt pathway and affect endothelial function . Meanwhile, in euthyroidism, hyperthyroidism, or hypothyroidism, researchers also found that THs were closely related to the endothelial function . Finally, THs were found to positively regulate cardiac myocyte β1‐adrenergic receptors in rat experiments and activate the renin‐angiotensin‐aldosterone system …”
Section: Introductionmentioning
confidence: 99%
“…β1-adrenergic blockade was associated with normalization of total arterial stiffness [28]. Our previous report of low-grade inflammation in subclinical hyperthyroidism has been confirmed by a recent study [41]. Vascular inflammation causes degradation of collagen and elastin, evokes changes in the proteoglycan composition and hydration status, and results in medial calcification [42] leading to increased arterial stiffness.…”
Section: Powered By Editorial Manager® and Produxion Manager® From Armentioning
confidence: 70%
“…Another proposed benefit of the use of TPE in TS includes the removal of inflammatory mediators or other humoral substances contributing to TS pathophysiology . Cytokines that include IL‐1, IL‐6, and TNF‐alpha, are frequently elevated in thyrotoxicosis and promote cytokine‐mediated tissue injury . TPE has been shown to significantly reduce cytokine concentrations in a number of disease entities, including sepsis .…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Cytokines that include IL-1, IL-6, and TNF-alpha, are frequently elevated in thyrotoxicosis and promote cytokinemediated tissue injury. 23,24 TPE has been shown to significantly reduce cytokine concentrations in a number of disease entities, including sepsis. [25][26][27] This reduction is rapid, but temporary.…”
Section: Discussionmentioning
confidence: 99%